Common stocks & common sense : the strategies, analyses, decisions, and emotions of a particularly successful value investor - Wachenheim, Edgar, III (John Wiley & Sons, Inc., 2022)
"Ed Wachenheim is one the most well-respected investors on Wall Street as founder, chairman and CEO of Greenhaven Associates for the past 28 years. Between 1990 and 2021, a typical portfolio of stocks that he managed enjoyed an average annual return of 19%, achieved with relatively conservative stocks and without the use of financial leverage. Wachenheim now wishes to share his investment strategies and experiences in an educational book on common stock investing so that others can benefit from his know-how. Wachenheim will teach the reader about common stock investing by writing about and analyzing actual investments that he, and other successful investors, have made. The core of the book is eleven chapters that each describe, in detail, an investment made by Greenhaven over the years, spanning the entire investment process. Wachenheim will start with a chapter that describes his basic investment strategy before delving into specific cases, covering topics like investing creatively and risk reduction"--